2015
DOI: 10.1111/beer.12089
|View full text |Cite
|
Sign up to set email alerts
|

Tensions between politico‐institutional factors and accounting regulation in a developing economy: insights from institutional theory

Abstract: The study contributes to building an understanding of the impact of political forces on the information environment of listed firms in a developing economy. Specifically, it investigates the tensions between politico‐institutional factors and accounting regulation on the prolonged and incomplete implementation of the International Financial Reporting Standards (IFRS) in Bangladesh from 1998 to 2010. Two phases of interviews were conducted in 2010–2011 and IFRS‐related enforcement documents from 1998 to 2010 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 99 publications
(224 reference statements)
6
38
0
1
Order By: Relevance
“…; Egels‐Zandén et al . ; Nurunnabi ). As a result, they have to manage these conflicts caused by pluralism to gain ‘legitimacy’ in order to obtain stakeholder support and resources to ensure their survival.…”
Section: Literature Reviewmentioning
confidence: 99%
“…; Egels‐Zandén et al . ; Nurunnabi ). As a result, they have to manage these conflicts caused by pluralism to gain ‘legitimacy’ in order to obtain stakeholder support and resources to ensure their survival.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Institutional theory suggests that business practices and organisational behaviour are influenced by institutional structures that are affected by political, social, economic and cultural forces (Nurunnabi, 2015). Equally, private organisations are renowned for operating in a domain and a context that is different from the public sector and thus would be generally be subject to differing regulatory requirements.…”
Section: Institutional Theorymentioning
confidence: 99%
“…Research has suggested that regulatory compliance, particularly in a procurement context, generally differs across the business sectors and various industries (Nurunnabi, 2015;Theodorakopoulos, Ram, & Kakabadse, 2015). It was therefore important to understand the impact of regulatory compliance on sustainability, within the public and the private sector.…”
Section: Research Hypothesismentioning
confidence: 99%
“…First, an institutional approach views corporations as social actors with social relations, and calls for studies that go beyond the firm-level explanation towards an institutional understanding of business-society relations (Abreu et al, 2015;Campbell, 2007;Nurunnabi, 2015). In an increasingly globalised world where corporations and industries operate across national borders, the unit of analysis should go beyond the focal firm and account for the interrelationships between the national socio-economic setting, the transnational markets in which the MNCs and large firms operate (Matten and Moon, 2008) and not least the broader global context of CSR ( Jamali and Neville, 2011).…”
Section: Csr In Afghanistanmentioning
confidence: 99%
“…Such isomorphic mechanisms are widely used in the CSR literature to bring in diverse 170 SAJGBR 5,2 explanations on the rise and impact of CSR. While some studies focus on the role of isomorphism to explain the emergence of CSR in relation to state pressures in BRICS (Abreu et al, 2012(Abreu et al, , 2015, the MNC headquarters pressures (Bondy et al, 2012) or pressures by employees and civil society (Reimann et al, 2012), others relate to the impact of isomorphism to corporate social and financial performance (Ilhan-Nas et al, 2015;Nurunnabi, 2015), to competitive advantage (Misani, 2010) and explore whether isomorphic pressures comprise a process of conformity or differentiation ( Johansen and Nielsen, 2012). We take the discourse further by arguing in this paper that a focus on isomorphism cannot stay unconnected to a specific and delimited field.…”
Section: The Analytical Framework For Explaining Csrmentioning
confidence: 99%